PENGARUH RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI PERIODE 2018 - 2021 - Saeful Nurfalah; Rumiasih Rumiasih; Muhammad Nur Rizqi (JURNAL PUNDI, 2023)
This study aims to determine the effect of Return on Assets and Return on Equity on Dividend Policy partially and simultaneously in consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2018-2021. The population of this study is all consumer goods industrial sector companies listed on the IDX during 2018-2021. This research uses purposive sampling method with certain criteria in order to obtain a sample of 18 companies in the consumer goods industry sector. The data analysis method used is descriptive statistical method, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of research conducted partially show that Return on Assets has a significant negative effect on Dividend Policy and Return on Equity has a significant positive effect on Dividend Policy. Meanwhile, the results of research conducted simultaneously show that Return on Assets and Return on Equity have a significant effect on Dividend Policy together.Keyword : Return on Assets, Return on Equity, Dividend Policy